2018
DOI: 10.3389/fnhum.2018.00416
|View full text |Cite
|
Sign up to set email alerts
|

Can Transcranial Direct-Current Stimulation Alone or Combined With Cognitive Training Be Used as a Clinical Intervention to Improve Cognitive Functioning in Persons With Mild Cognitive Impairment and Dementia? A Systematic Review and Meta-Analysis

Abstract: Background: Transcranial direct-current stimulation (tDCS) facilitates cognitive improvement in healthy and pathological populations. It has been increasingly used in cases of mild cognitive impairment (MCI) and dementia. Our research question is: Can tDCS serve as a clinical intervention for improving the cognitive functions of persons with MCI (PwMCI) and dementia (PwD)?Objective: This systematic review evaluated the evidence to determine the efficacy of tDCS in improving cognitive outcomes in PwD and PwMCI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 45 publications
5
36
2
Order By: Relevance
“…This study provides evidence that a-tDCS to the left frontal cortex does affect cognitive-neural changes in MCI, but not in a direction that supported a view that tDCS presented just prior to cognitive training elevated higher-order cognitive training benefits or served to ameliorate cognitive dysfunction. That is, the loci and timing of stimulation adopted in the present study did not replicate prior findings suggesting a potential modifying effect of tDCS on MCI (Meinzer et al, 2015; Yun et al, 2016; Murugaraja et al, 2017; Gonzalez et al, 2018). Future work is needed to examine precisely what happens to brain when tDCS is applied using fMRI studies to better understand the action of tDCS at the neuronal level.…”
Section: Resultscontrasting
confidence: 92%
“…This study provides evidence that a-tDCS to the left frontal cortex does affect cognitive-neural changes in MCI, but not in a direction that supported a view that tDCS presented just prior to cognitive training elevated higher-order cognitive training benefits or served to ameliorate cognitive dysfunction. That is, the loci and timing of stimulation adopted in the present study did not replicate prior findings suggesting a potential modifying effect of tDCS on MCI (Meinzer et al, 2015; Yun et al, 2016; Murugaraja et al, 2017; Gonzalez et al, 2018). Future work is needed to examine precisely what happens to brain when tDCS is applied using fMRI studies to better understand the action of tDCS at the neuronal level.…”
Section: Resultscontrasting
confidence: 92%
“…This finding corroborates previous results reported by Lawrence et al [45], Murugaraja et al [90], or metaanalyses [83], who revealed a medium effect size for memory for immediate effects. Mean improvement did not persist on follow-up, also in line with our findings.…”
Section: Effects Of Atdcs On Training Successsupporting
confidence: 93%
“…No sustained beneficial effects were found in the present study for delayed memory in either HE or MCI patients, which would be important for therapeutic application. Even though our results correspond to the meta-analysis as discussed above [83], it is at odds with studies that noted more sustained effects [42,45]. Differences may be related to variations in study specific parameters including number of sessions, and stimulation intensities.…”
Section: Effects Of Atdcs On Long-term Memorycontrasting
confidence: 64%
“…Transcranial direct current stimulation (tDCS) is a noninvasive neuromodulation technique that delivers a constant low-intensity subthreshold direct current to specific regions of the brain through electrodes placed on the scalp, thereby regulating cell transmembrane potential depolarization and hyperpolarization (Bindman et al, 1962;Nitsche and Paulus, 2000) and altering neuronal activity and excitability of the cerebral cortex (Nitsche et al, 2008;Stagg et al, 2018). A number of clinical and basic studies have found that tDCS treatment can improve memory and cognitive dysfunction in patients and animal with AD (Yu et al, 2014;Hsu et al, 2015;Liu et al, 2017;Cruz Gonzalez et al, 2018). However, few studies have validated tDCS in the preclinical AD phase, and little is known about the mechanism of action.…”
Section: Introductionmentioning
confidence: 99%